Purified Konjac Glucomannan as Thickener for Substituting Gelatin in Making Panna Cotta - Rachmaniah, Orchidea; Juliastuti, Sri Rachmania; Wisnu, Mita Mellenia; Samparia, Dian Asrini; Hendrianie, Nuniek; Darmawan, Raden; Meka, Wahyu; Fahmi, Fahmi (Halal Center ITS, 2024)
A thickener such as gelatin is essential in increasing viscosity and forming a gel system. Nowadays, gelatin is one of the most popular thickeners in food, pharmacy, and cosmetic products. Animal skins which lead to halal issues are still common sources of gelatin. Crude konjac flour (CKF) which is sourced from porang tubers and has a high degree of purity of glucomannan (GM) is a potential substitute for animal skins. Moreover, the use of KGM also supports national programs of processing agricultural products into finished products ready to export. This study applies five different CKF variants as panna cotta (PC) thickener: CKF from the fresh bulb of porang (Amorphophallus oncophyllus sp.) (CH-UP), CKF from chips of Porang (CH-CP), a native CKF, as well as laboratory-purified products of CKF (>90%-w of GM content) (DM-CKF-M3X-50, and DM-CKF-M3X-96), and commercially products of porang flour (K-TPO and K-TPM) were applied to make PC; substituting gelatin. Only CKF, DM-CKF-MX-50, and DM-CKF-M3X-96 successfully thickened PC in terms of appearances. Further, organoleptic analysis was applied to CKF, DM-CKF-MX-50, and DM-CKF-M3X-96. According to the organoleptic analysis, PC with CKF, DM-CKF-MX-50, and DM-CKF-M3X-96 was more preferred by the respondents than commercial PC. In overall, CKF application on PC exhibited improved sensory properties and tastes of PC.